Forecasting multi-step-ahead reservoir monthly and daily inflow using machine learning models based on different scenarios - Ibrahim K.S.M.H.; Huang Y.F.; Ahmed A.N.; Koo C.H.; El-Shafie A. (Springer, 2023)
Adaptive boosting; Decision making; Forecasting; Fuzzy inference; Fuzzy neural networks; Fuzzy systems; Multilayer neural networks; Multilayers; Reservoirs (water); Water resources; Adaptive neuro-fuzzy inference; Adaptive neuro-fuzzy inference system; Extreme gradient boosting (XG-boost); Gradient boosting; Grid search; Grid search optimizer; Hyper-parameter; Inflow forecast; Machine-learning; Multilayer perceptron neural network; Multilayers perceptrons; Neuro-fuzzy inference systems; Perceptron neural networks; Search optimizer; Support vector regression; Support vector regressions; Machine learning